Crónicas de la afronegritud en América : la autonomía interpretativa de los afrodescendientes en la tradición cristiana - Leyva, Pedro Acosta (2009)
The author on this work examines the Christian theological legacy of the Africans and their descendants in America. In the first chapter he makes a synthesis of the Afro-blacks origin that goes back to the beginning of Mankind, goes through the Egyptian Civilization, revises the records about the journeys of Africans to America in the past, and interprets the theories that define the reasons of the black slavery in America. In the two following chapters, the author draws a chronological line regarding the events, the circumstances, and the discourses that show the Afro-blacks Christian interpretative autonomy in America.